Blended learning: Investigating its potential in an English language teacher training program - Kocoglu, Zeynep; Ozek, Yesim; Kesli, Yesim (Australasian Journal of Educational Technology, 2011)
Although the benefits of blended learning have been well documented in educational research, relatively few studies have examined blended learning in language teacher education. This study discusses a blended learning approach for a teacher training program designed for in-service English language teachers, and investigates its effectiveness by comparing with a face to face MA Program in English Language teaching. The research involved 39 in-service English language teachers, with 12 studying in a blended course (i.e., they received face to face instruction in the classroom and used web-based materials) and 27 in a traditional classroom. Results indicated that there was no difference in content knowledge acquisition between teachers receiving blended instruction and teachers receiving face to face instruction.